Pengaruh Sistem Informasi Manajemen Terhadap Pengambilan Keputusan Berbasis Data di Lembaga Pendidikan Nonformal - Nadhifa Salsabilla Bakris; Muhammad Irwan Padli Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In the digital era, efficient and effective data management is key for non-formal education institutions, especially kindergartens. This research explores the influence of Management Information Systems (MIS) on data-driven decision-making, which is essential for improving the quality of education. Using a qualitative approach, data was collected through a literature review that included books and scientific articles. The results show that SIM implementation enables managers to collect, store and analyse student data more systematically, increasing transparency and supporting better planning of learning programmes. However, challenges such as limited understanding of technology among staff and resource constraints were also identified. Overall, SIM has a significant impact on operational efficiency and decision-making in kindergartens, providing opportunities to improve the quality of education in the future